Immotthia atrograna (Dacampiaceae, Ascomycota), a new for Ukraine fungicolous fungus from the Carpathians - Akulov, O.Yu.; Hayova, V.P. (Український ботанічний журнал, 2016)
The paper reports first records of new for Ukraine genus and species of fungicolous fungi, Immotthia atrograna
(Cooke & Ellis) M.E. Barr. All collections were made in old-growth forests within protected areas in the Ukrainian
Carpathians during recent mycological surveys. The fungus was found to be associated with two xylariaceous species,
Annulohypoxylon cohaerens (Pers.) Y.M. Ju, J.D. Rogers & H.M. Hsieh and A. multiforme (Fr.) Y.M. Ju, J.D. Rogers et
H.M. Hsieh. Diagnostic description, nomenclature data, geographical distribution and original illustrations for both
sexual and asexual morphs of the reported species are provided. Morphologically similar fungicolous fungi are briefly
reviewed and compared. Повідомляється про перші знахідки в Україні мікофільного гриба Immotthia atrograna (Cooke & Ellis) M.E. Barr.
Усі зразки зібрані в старовікових лісах під час мікологічних обстежень на природоохоронних територіях Українських Карпат. Гриб знайдений на двох видах грибів —
Annulohypoxylon cohaerens (Pers.) Y.M. Ju, J.D. Rogers
& H.M. Hsieh і A. multiforme (Fr.) Y.M. Ju, J.D. Rogers &
H.M. Hsieh. Наведено діагностичний опис, номенклатурні дані, географічне поширення та оригінальні ілюстрації, а також вміщено стислі відомості для порівняння з морфологічно подібними мікофільними грибами. Сообщается о первых находках в Украине микофильного гриба Immotthia atrograna (Cooke & Ellis) M.E. Barr. Все
образцы собраны в старовозрастных лесах во время микологических обследований на природоохранных территориях Украинских Карпат. Гриб обнаружен на двух
видах грибов — Annulohypoxylon cohaerens (Pers.) Y.M. Ju,
J.D. Rogers & H.M. Hsieh и A. multiforme (Fr.) Y.M. Ju,
J.D. Rogers & H.M. Hsieh. Приведены диагностическое
описание, номенклатурные данные, географическое
распространение и оригинальные иллюстрации, краткие сведения для сравнения с морфологически сходными микофильными грибами.